Question and Answers Forum

All Questions      Topic List

Trigonometry Questions

Previous in All Question      Next in All Question      

Previous in Trigonometry      Next in Trigonometry      

Question Number 205403 by BaliramKumar last updated on 20/Mar/24

Answered by Rajpurohith last updated on 20/Mar/24

Clearly cot^2 (A)(1+cot^2 (A))=1  i.e,cot^2 (A)(cosec^2 (A))=1  ⇒((cos^2 (A))/(sin^4 (A)))=1   or cos^2 (A)=sin^4 (A)=(1−cos^2 (A))^2   or cos^2 (A)=1+cos^4 (A)−2cos^2 (A)  ⇒cos^4 (A)−3cos^2 (A)=−1

Clearlycot2(A)(1+cot2(A))=1i.e,cot2(A)(cosec2(A))=1cos2(A)sin4(A)=1orcos2(A)=sin4(A)=(1cos2(A))2orcos2(A)=1+cos4(A)2cos2(A)cos4(A)3cos2(A)=1

Commented by BaliramKumar last updated on 20/Mar/24

thanks

thanks

Terms of Service

Privacy Policy

Contact: info@tinkutara.com